PENGARUH KONTEN KREATOR INI VINDY PADA CHANNEL MY ACNE STORY TERHADAP KEPERCAYAAN DIRI REMAJA ACNE FIGHTER - Urbach, Nurul Vidya; ', Suyanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
My Acne Story channel is a story of the Acne Fighter's process to recover from acne skin problems. This channel also contains tips to cure acne. The platform for sharing stories of the struggle to recover from acne is YouTube social media. One of them is on Channel My Acne Story owned by creator Ini Vindy. The purpose of this study is to determine whether or not there is an influence of Ini Vindy's Creator Content on the My Acne Story Channel on the self-confidence of Acne Fighter teenagers. The theory used is S-R Theory (Stimulus Response). Using quantitative methods with an explanatory approach. The population in this study were viewers of Ini Vindy's My Acne Story Channel. Determination of the sample in this study using purposive sampling technique using the Isaac and Michael table obtained a sample size of 272 people. This study collected data by distributing questionnaires online (google form) on social media and analyzing the data with SPSS windows version 25. The results of the study based on statistical calculations, the hypothesis in this study is that there is an influence between Ini Vindy's Creator Content on My Acne Story Channel on Acne Fighter Teen Self-Confidence, then Ha is accepted and H0 is rejected. Based on the test results of the coefficient of determination (R2), it can be seen that the magnitude of the correlation value is R of 0.364 in the category of influential count. From this output, the coefficient of determination (R2) is 0.133. T his figure shows the effect of Ini Vindy's Content Creator on My Acne Story on Acne Fighter Teen Self-Confidence by 13.3% with a very weak category and a significant effect because it is greater than sig.> 0.05. While the remaining 86.7% is influenced by other variables not examined. Keywords: effect, content creator, self-confidence, acne fighter teenagers